EVALUATING THE LONG-TERM HEALTH EFFECTS OF EXPOSURE TO ENDOCRINE-DISRUPTING CHEMICALS. - Amjad Abdullah Ashri Aldrees,Khalid Alhumaidi Alanazi, Kholud Abdullah Alnekhilan, Bashaier Eid Alshibani , Abdulkarim Bandar Almutairi (Chelonian Research Foundation, 2023)
Endocrine-disrupting chemicals (EDCs) have been a growing concern in recent years due to their potential long-term health effects on humans. This essay evaluates the research on the long-term health impacts of exposure to EDCs. The methodology includes a review of current literature on the topic, focusing on epidemiological studies, animal studies, and toxicology research. The discussion highlights key findings from various studies and their implications for human health. Overall, the essay concludes that exposure to EDCs can have significant long-term health effects, including hormonal disruptions, reproductive issues, and increased risk of chronic diseases. Keywords: endocrine-disrupting chemicals, health effects, long-term exposure, hormones, reproductive health